2014
DOI: 10.5007/1980-0037.2014v16n5p563
|View full text |Cite
|
Sign up to set email alerts
|

Influência da distância de corrida na pressão plantar

Abstract: -Running is a popular sport performed at different places and involving different distances and modalities. Long distance running promotes cumulative loading on joints and soft tissues that could determine important biomechanical alterations. A tool for assessing such loads is the measurement of plantar pressure. Here we compared static plantar pressure before and after 10 km and 21 km running competitions. Twenty trained runners participated in this study. They were assigned to 10 km (n=10) or 21 km (n=10) gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
2
2
0
Order By: Relevance
“…We observed that after both shod and barefoot running plantar pressure increases in the midfoot and decreases in the rearfoot, which is in agreement with previous reports on the acute effects of running on plantar pressure [3,5]. The similar plantar pressures after shod and barefoot running may rely on the fact that the participants in this study were physically active subjects, and none had experience with running.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We observed that after both shod and barefoot running plantar pressure increases in the midfoot and decreases in the rearfoot, which is in agreement with previous reports on the acute effects of running on plantar pressure [3,5]. The similar plantar pressures after shod and barefoot running may rely on the fact that the participants in this study were physically active subjects, and none had experience with running.…”
Section: Discussionsupporting
confidence: 92%
“…However, although tissue stresses experienced during walking may be of interest in the study of sensorial disorders (e.g., diabetes), it is during running that increased load is experienced and higher lower extremity injury rates are observed [4]. Also, previous studies have shown that distance running leads to changes in plantar pressure as evidenced by static measures of plantar pressure [3,5].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…There were no significant changes found in the foot pressure distribution pre and post training which is similar to the results found by Rocha et al (2014), where they concluded that static assessment of plantar pressure are less sensitive after 21 km and more sensitive after 10 km. Thus, as the runners in the current study ran more than 30 km, this could be the reason behind the non-significant change in foot pressure distribution after training.…”
Section: Static Foot Pressure Distribution Of the Long Distance Runne...supporting
confidence: 85%